Lake Superior's summer cooling of shorelines and adjacent inland forests: Implications for refugia of boreal forests and disjunct arctic–alpine plants - Ashley Hillman; Scott E. Nielsen (Ecology and Evolution, 2023)
Abstract Climate refugia can serve as remnant habitat for cold‐adapted species and delay forest transitions. The world's largest freshwater lake by surface area, Lake Superior, serves as a model system for understanding cooling‐mediated refugia effects, as its cool summer water temperatures have maintained disjunct populations of arctic–alpine plants on its shoreline since deglaciation. It is known to affect local inland climates by providing a summer cooling effect; however, the inland temperature gradient and spatial patterns of cooling have not been well quantified. Here, we describe the extent, degree, and patterns of temperature buffering and examine drivers of buffering and disjunct plant occurrence for Lake Superior's north shore over a 3‐year period at distances of 10, 100 m, 1, 10, and 100 km inland. We analyzed temperature data by year, month, summer maximum (July), and growing degree days (GDD0) for each site. Average summertime cooling at shore sites (10 m) was ~5°C cooler than reference sites (100 km inland), with a maximum difference of −19.2°C. The magnitude of cooling varied geographically, with sites further west and southeast showing little to no cooling effect, while the exposed north‐central shore showed the highest degree of buffering (5.8°C cooler) and had a shorter growing season than reference sites. Finally, north‐central shorelines had fewer days above 16°C, a threshold above which disjunct plants are unlikely to grow. These sites also showed the highest proportion of disjunct arctic–alpine species, reflecting the highest buffering from inland sites. On north‐central shores, sites up to 10 km inland had less than 10 days per year warmer than 20°C, a threshold identified for boreal forest transition. An understanding of the extent of lake‐mediated cooling on adjacent forests can better inform the risk to disjunct species, inland forests, and vegetation transition models on Lake Superior's north shore.